2020
DOI: 10.21203/rs.3.rs-24611/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV positive status disclosure to a sexual partner: the influence of marital status and partner communication

Abstract: Background: Disclosure of HIV serostatus to sexual partner does not only facilitate partner's support and testing, but it also correlates with better treatment outcomes. We drew from a cross-sectional survey conducted among postpartum women with HIV to examine the rate of serostatus disclosure to sexual partners, the influence of relationship status, and knowing one's partner's status on disclosure and reasons for non-disclosure. Methods: We conducted telephonic interviews with a final sample of 485 postpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This report is in agreement with [24], who reported a nonsignificant decrease in haemoglobin concentration of rats treated with NaF alone in comparison with the control group. [25,26] reported that reduced blood platelets affect the viscosity of blood, which is correlated positively to blood pressure. Concomitant administration of NaF and A. muricata extracts for 30 days adversely affected the count of blood platelets which may produce a positive effect on the viscosity of blood.…”
Section: Histology Resultsmentioning
confidence: 99%
“…This report is in agreement with [24], who reported a nonsignificant decrease in haemoglobin concentration of rats treated with NaF alone in comparison with the control group. [25,26] reported that reduced blood platelets affect the viscosity of blood, which is correlated positively to blood pressure. Concomitant administration of NaF and A. muricata extracts for 30 days adversely affected the count of blood platelets which may produce a positive effect on the viscosity of blood.…”
Section: Histology Resultsmentioning
confidence: 99%